MENINGKATKAN PERILAKU PROAKTIF KARYAWAN MELALUI PERAN PIMPINAN DAN SISTEM KONTROL - Nurofi, Achmad (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2014)
The purpose of this study was to examine the relationship between leadership role and control system and staff proactive behavior.This study uses primary data. Data taken directly from the respondents by using questionnaire technique in star Hotel Semarang that are the object of research. Data were analyzed by simple regression analysis and residual test.The results showed that suggests that leadership role and control system significantly affect staff proactive behavior.